Footprint analysis of CO2 in microbial community succession of raw milk and assessment of its quality - Zheng, Anran; Liu, Jun; Wang, Mengsong; Bu, Ningxia; Liu, Dunhua; Wei, Chaokun (Frontiers in Nutrition, 2023)
With the growing production of raw milk, interest has been increasing in its quality control. CO2, as a cold processing additive, has been studied to extend the cold storage period and improve the quality of raw milk. However, it is yet uncertain how representative microbial species and biomarkers can succeed one another at distinct critical periods during refrigeration. Therefore, the effects of CO2 treatment on the succession footprint of the microbial community and changes in quality during the period of raw milk chilling were examined in this study. The refrigeration time was shown to be prolonged by CO2 in a concentration-dependent way. According to 16S rRNA analysis, CO2 treatment was linked to substantial variations in beta and alpha diversity as well as the relative abundances of various microbial taxa (P < 0.01). The dominant bacterial phylum Proteobacteria was replaced with Firmicutes, while the major bacterial genera Acinetobacter and Pseudomonas were replaced with lactic acid bacteria (LAB), including Leuconostoc, Lactococcus and Lactobacillus. From the perspective of biomarkers enriched in CO2-treated sample, almost all of them belong to LAB, no introduction of harmful toxins has been found. The assessment of the quality of raw milk revealed that CO2 improved the quality of raw milk by lowering the acidity and the rate of protein and fat breakdown, and improved the flavor by reducing the generation of volatiles, and increasing umami, richness, milk flavor and sweetness, but reducing sourness.These findings offer a new theoretical foundation for the industrial use of CO2 in raw milk.